2014
DOI: 10.1097/fjc.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

The Cardioprotective Effects of Novel Na+/H+ Exchanger Inhibitor TY-51924 on Ischemia/Reperfusion Injury

Abstract: The inhibitory effects of sodium 3-guanidinocarbonyl-2-methyl-6,7,8,9-tetrahydro-5H-cyclohepta[b]pyridine-9-ylmethyl sulfate monoethanolate (TY-51924) are selective for Na(+)/H(+) exchanger (NHE)-1 in PS120 cells expressing human NHE isoforms assayed by NH(4)Cl prepulse technique. The median inhibitory concentrations (micromolar) of TY-51924 were 0.095 ± 0.008 (NHE-1), 0.621 ± 0.093 (NHE-2), and >100 (NHE-3). In anesthetized dogs subjected to 90 minutes ischemia/300 minutes reperfusion, intravenous bolus TY-51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…A recent study by Sasamori et al reported marked dose-dependent reduction in myocardial infarct size in dogs (90-minute ischemia and 300-minute reperfusion) with TY-51924 (selective NHE1 blocker) administered before reperfusion. 69 Maximum protection was provided when TY-51924 was given continuously before reperfusion and maintained thereafter. While the reasons for these different results are not clear, it is possible that distinct enzyme or receptor affinities of NHE1 blockers are responsible for the diverse results.…”
Section: Implication Of Nhe1 In Ischemia-reperfusion Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Sasamori et al reported marked dose-dependent reduction in myocardial infarct size in dogs (90-minute ischemia and 300-minute reperfusion) with TY-51924 (selective NHE1 blocker) administered before reperfusion. 69 Maximum protection was provided when TY-51924 was given continuously before reperfusion and maintained thereafter. While the reasons for these different results are not clear, it is possible that distinct enzyme or receptor affinities of NHE1 blockers are responsible for the diverse results.…”
Section: Implication Of Nhe1 In Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Optimal timing, dosage, plasma concentration, and mode of drug delivery also contribute markedly to potential efficacy; this was clearly shown by Sasamori et al in their study. 69 Bioavailability within the first minutes of reperfusion is critical to affect the following factors: 1-change in cellular Ca 2þ homeostasis, 2-control of intracellular pH postreoxygenation of ischemic myocytes, and 3-signaling pathways that involve Ca 2þ equilibrium or myofibrillar Ca2þ sensitivity. 82 Lack of presence of the inhibitor in the early minutes of ischemia or reperfusion markedly reduces the likelihood of a beneficial effect.…”
Section: Limitationsmentioning
confidence: 99%
“…TY-51924 is a novel NHE inhibitor that was synthesized by introducing a water-soluble functional group to TY-12533, reported to have cardioprotective effects against ischemiareperfusion injury caused by NHE inhibition in rats [9]. After intravenous administration, TY-51924 showed low levels in central nervous tissue and was rapidly eliminated from blood and tissues in animal experiments [10]. In a canine ischemiareperfusion model, TY-51924 administered intravenously before reperfusion reduced infarct size [10].…”
Section: Introductionmentioning
confidence: 99%
“…After intravenous administration, TY-51924 showed low levels in central nervous tissue and was rapidly eliminated from blood and tissues in animal experiments [10]. In a canine ischemiareperfusion model, TY-51924 administered intravenously before reperfusion reduced infarct size [10]. TY-51924 was also well tolerated in Phase I trials and a small Phase IIa pilot trial [11].…”
Section: Introductionmentioning
confidence: 99%
“…After intravenous administration, TY-51924 penetrated to central nervous tissue at a low level in central nervous tissue and was rapidly eliminated from blood and tissues in animal experiments. In a canine ischemia-reperfusion model, TY-51924 administered intravenously before reperfusion reduced infarct size [13]. TY-51924 was also well tolerated in Phase I trials and a small phase IIa pilot trial [14].…”
mentioning
confidence: 95%